PSVII-3 Effects of Feeding Direct-fed Microbials on Digestibility and Rumen Fermentation Characteristics of Finishing Bos Indicus Cattle. (21st September 2022) - de Dias, Bruno Garcia Carvalho; Meschiatti, Murilo A; Brixner, Bárbara; Almeida, Alecsander; Cappellozza, Bruno; Copani, Giuseppe; Ferreira, Paulo; Queiroz, Oscar; Santos, Flavio
Abstract: Direct feed microbials (DFM) are probiotics often fed to feedlot to cattle offered to improve rumen fermentation and/or intestinal health, thus benefiting animal health and performance. We hypothesized that DFM supplementation would improve nutrient digestibility and rumen fermentation in finishing Bos indicus cattle. On day -1, 30 rumen-cannulated Nellore bulls were blocked based on initial body weight (BW; 350 ± 35.0 kg) in 1 of 30 pens and, within each block, animals were randomly assigned to: (1) Control: corn-based diet without DFM (n = 10), (2) EFSC: CONT + 1 gram/head per day of a DFM based on Enterococcus faecium and Saccharomyces cerevisiae (Probios Precise, Chr. Hansen A/S, Horsholm, Denmark; n = 10), and (3) BLBS: CONT + 2 grams/head per day of a DFM based on Bacillus licheniformis and Bacillus subtilis (Bovacillus, Chr. Hansen A/S; n = 10). The experimental period lasted 35 days, while between days 30 to 33, total fecal collection was performed and on days 34 and 35, feces and rumen fluid were collected at 0, 3, 6, 9, 12, 15, 18, and 21 h post-feeding for ammonia, VFA, and pH determination. All data were analyzed as orthogonal contrasts using SAS: (1) DFM vs. CONT and (2) EFSC vs. BLBS. Inclusion or type of DFM did not affect either nutrient digestibility or ruminal fermentation parameters (P ≥ 0.40). In contrast, DFM supplementation, regardless of type, yielded a reduced mean ammonia concentration (14.7 vs. 15.7 mg/L; P = 0.05). Moreover, ammonia concentrations were decreased in EFSC at 3 and 6 h post-feeding vs. CONT (P ≤ 0.04), but also less for BSBL vs. CONT at 6 h (P < 0.01). In summary, DFM supplementation, regardless of type, reduced proteolysis, with no effect on other parameters of rumen fermentation in Bos indicus bulls fed a finishing diet.